Ultracold Long-Range Van Der Waals Rydberg Trimers - Herrera-Urbina, F (Nature Research, 2025)
Rydberg molecules are an essential ingredient of cold molecular sciences. Due to the richness of interactions between Rydberg atoms and neutral atoms, new kinds of Rydberg molecules and binding mechanisms are still to be discovered. In this work, we predict the existence of long-range van der Waals trimers in dilute atom-gas mixtures. These are bound states of a Rydberg atom and a diatomic polar molecule mediated by the long-range van der Waals interaction. This binding mechanism gives rise to trimers with sizes between 5 and 500 nm and binding energies between 0.2 kHz and 2 MHz depending on the atomic principal quantum number n and orbital angular momentum L. We show that these trimers can be produced via two-photon photoassociation, with rates on the order of (10−13 - 10−11) cm3s−1 for temperatures in the range of (0.5 μK - 10 μK), and discuss the feasibility of observing trimer resonances. © This is a U.S. Government work and not under copyright protection in the US; foreign copyright protection may apply 2025.